Indications, sub-types and complications of surgically treated thyroid disease in Africa: A systematic review and meta-analysis - Bekalu Getachew; Mekbeb Afework; Girmaye Tamrat (Surgery Open Science, 2025)
Objectives: Thyroidectomy is a surgical procedure that reduces or removes the thyroid gland the aim of this systematic review and meta-analysis was to assess the pooled prevalence and sub-types of thyroidectomy and characterize its postoperative complications in some low and middle income African countries. Methods: The studies were identified through an exhaustive search of reputable databases Twenty-two studies were selected based on the inclusion and exclusion criteria. Data were extracted using a standardized and pre-tested data extraction checklist, and the analysis was done using STATA version 14 statistical software. Heterogeneity was assessed using I2 statistics. Result: Toxic goiters were the most common indication for thyroidectomy accounting for 46.62 % of cases. Cosmetic reasons (41.07 %) and suspicion of malignancy (11.30 %) were the other common indications. Regarding surgical procedures, sub-total thyroidectomy (39.27 %) was the predominant surgical procedure, followed by lobectomy and isthmusectomy (34.88 %) and near-total thyroidectomy (34.77 %) respectively. The pooled prevalence of postoperative complications following thyroidectomy was 26.6 % [95%CI, 18.3–34.89]. Hypoparathyroidism (8.49 %) was the most common complication, followed by recurrent laryngeal nerve injury (7.96 %) and dysphonia (7.28 %). Conclusion: A toxic goiter was the most common indication for thyroidectomy. The pooled prevalence of postoperative complications was comparably higher than international figures. Hypoparathyroidism was the predominant postoperative complication.